Relation between periodontal disease and ischemic heart disease (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The aim of this study was to determine the association between periodontal diseases and ischemic heart disease among 30 exercise tolerance test (ETT) positive and 30 ETT negative of ischemic heart disease patients attending the National Heart Foundation Hospital and Research Institute. The presence of gum swelling for the two groups were statistically significant. The results revealed that 80% ETT positive and 23% ETT negative respondent had gum bleeding, 53% ETT positive and 7% ETT negative had ulceration of gingiva. Furthermore, severely inflamed with spontaneous bleeding was found in 53.3% ETT positive and 6.7% negative respondents. It can be concluded that oral hygiene should be promoted as a part of prevention of ischemic heart disease.